MODEL PEMBELAJARAN TWO-STAY TWO-STRAY BERBANTUANGEOGEBRA TERHADAP KEMAMPUAN KONEKSI MATEMATIS - riska ayu septianingrum; Eleonora dwi wahyuningsih; wikan budi utami (Department of Mathematics Education, Universitas Kuningan, 2019)
The background of this research was based on students’ lack of mathematical connection ability in learning. The aim of this research was to determine students’ mathematical connection ability through Two-Stay Two-Stray learning model assisted by Geogebra application was better than that on cube and cuboid subject. The type of this research was Experimental and Design of Intact-Group Comparison Research. The sampling technique of this research used Cluster Random Sampling and students of grade VIII D, VIII E, VIII F in SMP Negeri 3 Slawi were chosen as the samples. The technique of collecting data used interview, documentation, and test. The result of this research showed that students’ mathematical connection ability through Two-Stay Two-Stray learning model assisted by Geogebra application was better than that without Geogebra application proven by the t-test.